Critical uncertainty factors for efficient allocation of demand risk in privately financed public infrastructure projects in Australia. (22nd August 2011) - Jin, Xiao-Hua; Lee, Chyi Lin; Zhang, Guomin
Risk allocation in privately financed public infrastructure projects, which are mainly referred as public-private partnership (PPP) projects, is a challenging job due to the nature of incomplete contracting. Among the various risks that may eventually materialise, demand risk is one of the major challenges that PPPs face. Choosing a risk allocation strategy could be viewed as the process of deciding the proportion of risk management responsibility between public and private partners based on a series of characteristics of risk management service transaction in question. These characteristics are more or less related to the various uncertainty factors. In this study, various uncertainty factors have been examined in order to achieve efficient allocation of demand risk and minimise risk management-related costs in a long-term view. Critical uncertainty factors have been identified through an industry-wide survey in Australia. Future research directions are also set out.